Development of Standard Formulations for Porcelain Production from Ohiya Clay - Imagwuike, Ibeh M.; Ndukaa, Nwankwojike B.; Anthony, Obi I.; Nwadinobi P., Nwadinobi P.; Augustine, Lewachi A. (Kathmandu University Journal of Science Engineering and Technology, 2021)
Optimal designs for producing standard porcelains from Ohiya clay were developed in this study to scale up industrial utilization of this alumina-silicate dominated natural clay reserve. This involved experimental evaluation, modeling and optimization of the effects of firing temperature and varying Ohiya clay-feldspar-silica mix on the properties of porcelains produced from it using desirability optimization methodology. Apparent porosity, linear shrinkage, apparent density, water absorption rate, cold compressive strength and modulus of rupture constitutes the porcelains’ properties evaluated. Results revealed 42:32:20, 42:33:17, 41:32:27 as standard formulation of the clay, feldspar and silica into low/high voltage insulators, tiles and tableware respectively while 1250/1300°C, 1000°C and 1300°C constitute their respective optimal firing temperatures. Six hundred and twenty-five naira (₦625), three hundred and twenty-two naira(₦322), three hundred and fourty seven(₦347) wereused for producing an 11 kV electric insulator, 400×400 mm floor tile and serving dish based on these standard design respectively against their respective market prices of one thousand naira (₦1000), three hundred and fifty naira (₦350), four hundred and twenty naira (₦420) This implies 60%, 9% and 21% profit boost from the developed porcelain designs. Hence, adoption of the models/optimal formulations developed in study for porcelains’ production from ohiya clay is recommended for proficient exploitation of this natural resource.